Efetividade de um manual educativo no apoio prestado por acompanhantes em centro obstétrico: um ensaio clínico randomizado - Mendes, Igor Cordeiro (2019)
The objective of this research is to evaluate the effectiveness of an educational manual in the support provided by caregivers in an obstetric center. It is a Randomized Clinical Trial (RCT) that was conducted from November 2018 to October 2019, at the Assis Chateaubriand School Maternity Obstetric Center (ACSMOC) of Fortaleza-CE. Two groups were formed: Intervention Group (IG) - companions who participated in an intervention using the educational manual entitled “Preparing to accompany normal birth: what is important to know?”; Control Group (CG) - companions eligible to participate in the research who received routine guidance, ie guidance given in the delivery room by health professionals, academics, among others. In addition, the mothers who had their companions involved in this study, regardless of group, were also included. The sample consisted of 248 participants, with 62 companions for each group, totaling 124 companions. In addition, 124 postpartum women who had their companions included in this research were included. The following steps were developed: 1. Baseline; 2. Randomization; 3. Final Evaluation - Escorts and 4. Final Evaluation - Postpartum. In Phase 1, the Companion Characterization Form was used; In Phase 3, the Support Evaluation Form was used, highlighting the actions of physical, emotional, informational support and advocacy / intermediation; and in Phase 4, the form of evaluation of the experience and satisfaction of the postpartum with labor, which contains four subscales of the Experience and Satisfaction with Childbirth Questionnaire (QESP) (Positive Experience, Negative Experience, Relaxation and Support Companion) and the Brazilian Birth Companion Support Questionnaire (BCSQ), which contains information about the supportive activities provided to the parturient by the companion during hospitalization for childbirth. Data were analyzed using the Statistical Package for the Social Sciences (SPSS), version 24.0, using the Pearson and Fisher chi-square tests (categorical variables) and the Mann-Whitney test (continuous variables). Relative Risk (RR) and 95% confidence interval were calculated for the main dependent variables. The research was submitted to the ethics committee, obtaining approval opinion No. 3,046,203 (CAAE: 03011518.7.0000.5050). The companions had a median (Md) of 32 years old and 10 years of schooling, most of them mother, aunt or sister (n = 80; 64.5%) of the parturient. In step 1, it was found that 76 (61.3%) companions had knowledge about some parturient support action, predominating the physical (Md = 3) and emotional (Md = 2) support actions, with no statistically significant differences. between the groups. In step 3, regarding the evaluation of support provided by the companion in the delivery room, it was evidenced that accompanying women from the IG were more likely to develop, during the parturition process, the actions of physical, emotional, informational support and advocacy / intermediation, There was a statistically significant difference in all support dimensions when comparing the two groups, especially the hand-holding techniques, in which the participants of the IG had 19.60 (95% CI: 5.02-76.52) times more likely to develop such action; and the constant presence, which was 12.84 (95% CI: 4.26-38.70) times more performed by the same group. IG caregivers performed a greater number of supportive actions (20 vs 6; p: 0.001) and better evaluated the experience of following delivery (100.0 vs 74.2; p: 0.001). As for step 4, related to the evaluation of experience, satisfaction and social support reported by the mothers with labor and delivery, it was found that mothers accompanied by participants of the IG were more likely to demonstrate satisfaction with the way the work occurred. childbirth (96.8% vs 56.5%; RR 9.15; 95% CI: 2.38-35.18) and childbirth (96.8% vs 74.2%; RR 5.09; 95% CI : 1.36-19.01), who found the methods of relaxation to be useful in labor (88.7 vs 38.7; RR: 4.47; 95% CI: 2.23-8.97) and delivery (90.3 vs 45.2; RR: 4.44; 95% CI: 2.09-9.43), and to recognize the importance of support provided by the companion in labor (96.8 vs 62.9 RR: 7.57; 95% CI: 1.98-28.89), at delivery (90.3 vs 53.2; RR: 3.67; 95% CI: 1.74-7.73) and in the immediate postpartum period (96.8 vs 71.0; RR: 5.76; 95% CI: 1.53-21.70), reflecting a better experience and satisfaction with labor and delivery (125 vs 97; p: 0.000), according to the QESP Subscales analyzed here. It is concluded that the intervention applied in the maternity with the use of an educational manual was effective and contributes to a greater range of support provided by the companion. This reflected in a better assessment of the companion and the puerperal woman with the shared experience, demonstrating the relationship between the support provided by the companion and the support perceived and experienced by the parturient.